PERANCANGAN VIDEO PROMOSI KOLAM IKAN SAKTI SUNGAI JANIAH DI KABUPATEN AGAM - IIM KURNIA, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Sakti Sungai Janiah Fish Pond is a tourist attraction in West Sumatra Province. Sakti fish attraction has long been famous, the fish in the pond according to legend originated from humans, but in recent years visitors who have arrived have begun to decrease due to the many new tourist objects opened, this situation makes the authors interested in improving returning the number of visitors in the magical fish attraction by making a promotional video entitled "Sungai Janiah sakti fish tour".The approach methodology in designing this promotional video uses a qualitative approach, namely by understanding the information in a problem. So that the selection of promotional media is more effective, the message to be conveyed is easily understood by the target audience.The result of designing a promotional video for the Sungai Janiah sakti fish pond is a work in the form of videos that will be packed in full HD format and diburning on DVD discs, and for supporting media produced are DVD labels, DVD disc covers, shirts, stickers, key chain, pin, totebag and poster.Keywords: media promotion, nature tourism, legendary tourism, Sungai Janiah magic fish.